Verbal Autopsy of Swine Flu Confirmed Cases in Surat City - Prasad, Rachna; Verma, Anupam; Vasava, Bipin; Patel, N B; Patel, Amit; Kumar, Mukesh; Upadhyay, Asutosh (National Journal of Community Medicine, 2017)
Background: Delay in seeking treatment or delayed referral to higher centre, co-morbid conditions as well as low suspicion index in the early phases of epidemic were common reasons of poor patient outcome. Objective of the study was to assess the epidemiologic characteristics and high-risk profiles among reported deaths with H1N1 influenza in Surat city. Method: Verbal autopsy audit of 30 swine flu positive cases were carried by household visit and checking medical records from respected hospitals of Surat Municipal Corporation area as well as Tapi district. Results: Deaths were higher among age group of 18-45 years and among male population. Out of total 30 deaths, only 4 swine flu positive patients had reported to hospital within 48 hours after onset of signs & symptoms. More than 90%% swine flu death patients did not take Oseltamivir within 48 hours after onset of signs & symptoms. Diabetes, hypertension and IHD were major co morbid conditions associated with H1N1 fatality. Conclusion: Mortality was higher in patient having co-morbid conditions like hypertension, diabetes, and IHD. Longer interval between onset of signs and symptoms to diagnosis as well as referral and initiation of Oseltamivir may be the possible reason for higher mortality during swine flu epidemic 2017.